Tecnologie e composizione: alcune riflessioni - Solbiati, Alessandro (Musica/Tecnologia, 2010)
Alessandro Solbiati considers the values of computer music in terms of musical education, setting out the innovative elements through the filter of the analysis of his experience in relation to technology. Even in his case, the centrality of the composer – and the need for the technological contribution will always be ‘controlled’ by the composer’s vision and the compositional thought – is reaffirmed.